2021
DOI: 10.1140/epjc/s10052-021-09183-9
|View full text |Cite
|
Sign up to set email alerts
|

xPPN: an implementation of the parametrized post-Newtonian formalism using xAct for Mathematica

Abstract: We present a package for the computer algebra system Mathematica, which implements the parametrized post-Newtonian (PPN) formalism. This package, named xPPN, is built upon the widely used tensor algebra package suite xAct, and in particular the package xTensor therein. The main feature of xPPN is to provide functions to perform a proper $$3+1$$ 3 + 1 decomposition of tensors, as well as a perturba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…while the remaining parameters vanish again, indicating that the theory is fully conservative, i.e., there are no preferred-frame or preferred-location effects or violation of total energy-momentum conservation. Taking a closer look at this result, one finds that even in this class there is another subclass given by l Y = 0 corresponding to a minimally coupled scalar field at the linear perturbation order which leads to the general relativity values (39). Further, we find that for 4l 2 Y + l X l Q = 0 the PPN parameters β and γ diverge.…”
Section: Ppn Parametersmentioning
confidence: 64%
See 2 more Smart Citations
“…while the remaining parameters vanish again, indicating that the theory is fully conservative, i.e., there are no preferred-frame or preferred-location effects or violation of total energy-momentum conservation. Taking a closer look at this result, one finds that even in this class there is another subclass given by l Y = 0 corresponding to a minimally coupled scalar field at the linear perturbation order which leads to the general relativity values (39). Further, we find that for 4l 2 Y + l X l Q = 0 the PPN parameters β and γ diverge.…”
Section: Ppn Parametersmentioning
confidence: 64%
“…Potential deviations from these values are encountered only in the subclass l Y + l Z = 0. Within this subclass, we found that theories which in addition satisfy l X = l Y = 0, so that the scalar field is minimally coupled to nonmetricity at the linear order, again yield the same PPN parameters (39). For theories with 3l 2 Y + l X l Q = 0 we obtain the PPN parameters…”
Section: Ppn Parametersmentioning
confidence: 75%
See 1 more Smart Citation
“…In this article we will follow [77] by using the following syntax highlighting for code listings: keywords for Mathematica are typeset in green, for xAct in blue and for HiGGS in red. This paper uses the 'West coast' signature (+, −, −, −).…”
Section: A Conventionsmentioning
confidence: 99%
“…For instance, in TG, Refs. [32][33][34][35] have explored important parts of the decomposition of TEGR. On the other end of the spectrum, Refs.…”
Section: Introductionmentioning
confidence: 99%